Impact of diagnosis-related group payment on medical expenditure and treatment efficiency on people with drug-resistant tuberculosis: a quasi-experimental study design - Yingbei Xiong; Yifan Yao; Yuehua Li; Shanquan Chen; Yunfei Li; Kunhe Lin; Li Xiang (International Journal for Equity in Health)
Abstract Background The severe health challenge and financial burden of drug-resistant tuberculosis (DR-TB) continues to be an impediment in China and worldwide. This study aimed to explore the impact of Diagnosis-related group (DRG) payment on medical expenditure and treatment efficiency among DR-TB patients. Methods This retrospective cohort study included all DR-TB patients from the digitized Hospital Information System (HIS) of Wuhan Pulmonary Hospital and the TB Information Management System (TBIMS) with completed full course of National Tuberculosis Program (NTP) standard treatment in Wuhan from January 2016 to December 2022, excluding patients whose treatment spanned both before and after the DRG timepoint. These patients are all receiving standardized treatment specified by the NTP in designated tuberculosis hospitals. We performed the difference-in-differences (DID) model to investigate 6 primary outcomes. The cost-shifting behaviors were also examined using 4 outpatient and out-of-pocket (OOP) indicators. In the DID model, the baseline period is set from January 2016 to December 2020 before the DRG payment reform, while the treatment period is from January 2021 to December 2022. The payment reform only applied to individuals covered by Wuhan Municipal Medical Insurance, so the treatment group consists of patients insured by this plan, with other patients serving as the control group. Results In this study, 279 patients were included in the analysis, their average treatment duration was 692.79 days. We found the DRG payment implementation could effectively reduce the total medical expenditure, total inpatient expenditure, and inpatient expenditure per hospitalization by 28636.03RMB (P < 0.01), 22035.03 RMB (P < 0.01) and 2448.00 RMB (P < 0.05). We also found a reduction in inpatient frequency and inpatient length of stays per hospitalization by 1.32 and 2.63 days with significance. The spillover effects of the DRG payment on outpatient and OOP expenditure were statistically insignificant. Conclusions The DRG payment method can effectively control the increase of DR-TB patients’ medical expenditure and improve treatment efficiency with the guarantee of care quality. Furthermore, there was no evidence of spillover effects of DRG payment on outpatient and out-of-pocket expenditures.